Factors Driving the Abundance of Wintering Waterbirds in Coastal Areas of Guangdong Province, China - Yang, Xitao; Duan, Zhizhao; Li, Shuangshuang; Zhang, Chunxia; Qu, Ming; Hua, Guodong; Niu, Xiaonan; Hu, Huijian; Yu, Dongmei (Frontiers in Ecology and Evolution, 2022)
The diverse habitat of the coastal areas of Guangdong, China, support important waterbird populations, thereby contributing to the conservation of waterbirds in China and globally. The sensitivity of different waterbirds to environmental driving factors results in differences in habitat selection, which in combination affect waterbird abundance. This study investigated the effects of environmental and human disturbance factors on the abundance of waterbirds based on a survey of waterbirds in coastal areas of Guangdong Province, China. Redundancy Analysis (RDA) was mainly used to study the relationships between the abundance of waterbirds and environmental and human factors. The results showed that the areas of mangrove and tidal flats were the main factors driving the abundance of shorebirds and open water waterbirds, whereas the areas of mangrove and water bodies were the main factors driving the abundance of wading birds and waterfowl, respectively. Road length and the areas of construction land were found to have negative effects on the abundance of waterbirds. A waterbird protection and management strategy was proposed based on the results.